The Use of ICT and Its Challenges during the COVID-19 Outbreak: A Phenomenological Study of Junior High School Mathematics Teachers in Indonesia - Taufan, Mochammad; Nurafifah, Luthfiyati; Sudirman, Sudirman; Ilham, Topik (Jurnal Pendidikan MIPA, 2022)
This study aimed to describe the ICT products used and the difficulties experienced by junior high school mathematics teachers in Indramayu during online learning during the pandemic COVID-19. In this study, researchers used a phenomenological method based on observation, interview and documentation techniques. Data analysis in this study consisted of data reduction, data presentation and conclusion drawing using the application ATLAS.ti 8. ICT products used by junior high school mathematics teachers in Indramayu include; Zoom Meeting, YouTube, WhatsApp, PowerPoint, Google Meet, Google Form, Google Drive, Google Classroom, Geogebra and School Blogger. The results showed that the most widely used ICT product by data sources was the WhatsApp application. The difficulties of mathematics teachers during online learning are also very diverse, but the most common are network problems and internet quotas.Keywords: information and communication technology, online mathematics learning, learning difficulties, COVID-19.DOI: http://dx.doi.org/10.23960/jpmipa/v23i1.pp173-184